Profiling & mitigating brute force attack in wireless LAN / Mohammad Hafiz Mohd Yusof - Mohd Yusof, Mohammad Hafiz (2015)
Brute force is another dangerous type of cyber-attack meant for cracking wireless LAN WPA/WPA2 password. It preludes with several other attacks' attempts namely DeAuthentication, packet sniffing (airodump) and finally aircrack. The successful of a brute force attack is so determined by these attempts. This study will analyze DeAuthentication attack traffic pattern, sniffing and aircrack activity and propose two mitigation techniques which are 1) increase beacon time interval 2) mapping user's MAC address and finally evaluate its performance using normal distribution model. Experimental result shows that deployment of mitigation techniques is efficient to stop these activities and mitigate the brute force attack and in terms of performance it shows great number of processing time above mean value.